Single torradovirus infections explain the mysterious cassava frogskin disease in the Americas - Jimenez, Jenyfer; Caicedo, Sara; Pardo, Juan M.; Gil-Ordóñez, Alejandra; Alvarez-Quinto, Robert; Mollov, Dimitre; Cuellar, Wilmer J. (Nature Portfolio, 2024)
Cassava frogskin disease (CFSD) emerged in the Americas in the 1970s, but its causal agent has to date remained a mystery. The clonal propagation of cassava, high incidence of mixed infections, unknown alternative hosts, and root symptoms taking two or more crop cycles to develop, have made it difficult to identify the causal agent. Consequently, most studies on CFSD have produced a catalogue of pathogens occurring in affected plants. Using a sentinel approach, we captured single-pathogen infections in fields with high incidence of root symptoms. Eight months after being exposed to CFSD, we detected < 6.9% incidence of root symptoms in sentinel plants. Plants were then propagated and transferred to a screenhouse for a second infection cycle and storage root development. Interestingly, molecular diagnostics did not identify an association with phytoplasma or reovirids—pathogens historically reported in CFSD-infected plants—but indicated that single-infections by torradoviruses were sufficient to cause the disease. Further analysis by high-throughput sequencing confirmed the presence of torradoviruses in symptomatic roots and allowed unveiling the occurrence of a second torradovirus species in farmers' fields in Colombia. These new findings should support early interception of infected planting material, development of cassava seed certification standards, breeding and screening for resistance programs, and ultimately significantly reduce the impact of CFSD in cassava.